Penekuk Bambu Sistem Roll untuk Meningkatkan Kapasitas Produksi di Widya Handicraft Gintangan - Akhmad Afandi; Nuraini Lusi; Mohammad Nur Shodiq; Adetiya Prananda Putra (Politeknik Negeri Sriwijaya, 2021)
Handicraft from bamboo is a product of bamboo processing, which will later have to be shaped as desired so that it becomes a decoration or used item that has a selling value in the Gintangan area. The process from working bamboo to become a handicraft includes the following methods: cutting bamboo, splitting, cutting, bending, and finally, the weaving process. With the bamboo roll machine, it can use to turn the bamboo strips according to the wishes and needs of the craftsmen, so that this can help overcome difficulties in the process of bending the slices which have many size variations. This activity begins with the identification of problems with partners, planning the rolling machine, mentoring / counseling, and handing over tools. The result of this activity is to help craftsmen to accelerate the process of bending bamboo strips because the production capacity of bending is increased five times for a 5 mm thick slice and 120 times for a 0.25 mm slice thickness, thereby accelerating and accelerating production. Partners expressed hope that the activity would continue in the future because the process used was primarily manual.